Big Data and the Little Big Bang: An Epistemological (R)evolution - Balazka, Dominik; Rodighiero, Dario (Frontiers in Big Data, 2020)
Starting from an analysis of frequently employed definitions of big data, it will be argued that to overcome the intrinsic weaknesses of big data, it is more appropriate to define the object in relational terms. The excessive emphasis on volume and technological aspects of big data, derived from their current definitions, combined with neglected epistemological issues gave birth to an objectivistic rhetoric surrounding big data as implicitly neutral, omni-comprehensive and theory free. This rhetoric contradicts the empirical reality that embraces big data: 1) data collection is not neutral nor objective; 2) exhaustivity is a mathematical limit; 3) interpretation and knowledge production remain both theoretically informed and subjective. Addressing these issues, big data will be interpreted as a methodological revolution carried over by evolutionary processes in technology and epistemology. By distinguishing between forms of nominal and actual access, we claim that big data promoted a new digital divide changing stakeholders, gatekeepers, and the basic rules of knowledge discovery by radically shaping the power dynamics involved in the processes of production and analysis of data.